Effectiveness of an Interventional Program on Nurses Practices for Patient’s Undergoing Bariatric Surgery in Al-Sulaymaniyah Teaching Hospital - Soz Othman Aziz, Suad Jassim Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bariatric surgery (BS) is the most effective treatment for severe obesity, generally resulting in clinically significant weight loss, as well as improvement or resolution of related comorbidities, such as type 2 diabetes, and enhanced physical functioning and quality of life. Objectives: To determine the effectiveness of intervention program on nurses’ practices Methodology: A quasi-experimental study with quantitative design was carried out at the Surgical Teaching Hospital in Al- Sulaymaniyah City from the period of February of 2021 up to the end of march of 2022. Results: The findings of the study revealed that the intervention program was effective in the improvement in the modifying of practices about the preparation patients for bariatric surgery among nurses enrolled in the case group the study confirmed that there was no significant relationship between the effectiveness of intervention program on nurses knowledge & practices; and socio-demographic, and the Mean of square for practices study group pretest is125.92 and posttest is 145.88,for control group pretest is82.44,for posttest is 82.20. Conclusions: The study concludes that there is inadequate nurses practices in the (surgical ward) toward preparation of patients with bariatric surgery, and the effectiveness of the study sample after implementation intervention program. Recommendations: The study recommends to including the nurses for training courses to enhance their knowledge and practices. studies in this filed and increased the awareness about BS ,conducting further for large numbers of nurses to increase the awareness about BS.